Vegetation density and their impact on urban open spaces microclimate : a case study of KLCC Park, Kuala Lumpur, Malaysia / Wan Noor Anira Hj. Wan Ali@Yaacob, Norasikin Hj. Hassan and Ameri Mohd Sarip@Shariff - Hj. Hassan, Norasikin; Mohd Sarip@Shariff, Ameri; Hj. Wan Ali@Yaacob, Wan Noor Anira (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Urban open spaces are one of the characteristics of urban environment that is of enormous importance in the daily life of people living in urban areas. However, urban open spaces in tropical climate are highly exposed to solar radiation. These conditions will lead to increased global warming and urban heat island. Therefore, vegetation (trees) in urban areas is of special value as they can reduce the air temperature by direct shading of surface as well as by moderating solar heat gain through evapotranspiration of the trees. This study compares the effectiveness and influences of vegetation density (High, Medium and Low Density) on microclimate modification in improving ambient and human thermal comfort in urban open spaces. The study employed three (3) methods: (i) plant species selection procedure, (ii) a field measurement procedure and (iii) computer-based microclimate analysis (Temperature, Surface temperature and Relative humidity). The result from this study indicates that high vegetation, medium vegetation and low vegetation density of Peltophorum pterocarpum (Yellow Flame) species on 100 meter² have a different significance to direct microclimate on urban open spaces. The study found that the high vegetation density of the under turf and pavement of 100 meter² has more significance and influence on the microclimate modification in urban open spaces than the medium and low vegetation density due to the tree canopy. High vegetation density of Peltophorum pterocarpum (Yellow Flame) species of 100 meter² capability contributes to the reduction of the air temperature of up to 3.1 °C by promoting more evapotranspiration and effectively improving the ambience and outdoor thermal comfort in tropical urban open spaces.